Post-intervention acceptability of multicomponent intervention for management of hypertension in rural Bangladesh, Pakistan, and Sri Lanka- a qualitative study. - Tazeen H Jafar; Saeideh Tavajoh; H Asita de Silva; Aliya Naheed; Imtiaz Jehan; Chamini Kanatiwela de Silva; Nantu Chakma; Maryam Huda; Helena Legido-Quigley; COBRA-BPS Study Group (PLoS ONE)
Background COBRA-BPS (Control of Blood Pressure and Risk Attenuation-Bangladesh, Pakistan, Sri Lanka), a multicomponent, community health-worker (CHW)-led hypertension management program, has been shown to be effective in rural communities in South Asia. This paper presents the acceptability of COBRA-BPS multicomponent intervention among the key stakeholders. Methods We conducted post-implementation interviews of 87 stakeholder including 23 community health workers (CHWs), 19 physicians and 45 patients in 15 rural communities randomized to COBRA-BPS multicomponent intervention in in Bangladesh, Pakistan, and Sri Lanka. We used Theoretical Framework for Acceptability framework (TFA) with a focus on affective attitude, burden, ethicality, intervention coherence, opportunity cost, perceived effectiveness and self-efficacy. Results COBRA-BPS multicomponent intervention was acceptable to most stakeholders. Despite some concerns about workload, most CHWs were enthusiastic and felt empowered. Physicians appreciated the training sessions and felt trusted by their patients. Patients were grateful to receive the intervention and valued it. However, patients in Pakistan and Bangladesh expressed the need for supplies of free medicines from the primary health facilities, while those in Sri Lanka were concerned about supplies' irregularities. All stakeholders favoured scaling-up COBRA-BPS at a national level. Conclusions COBRA-BPS multicomponent intervention is acceptable to the key stakeholders in Bangladesh, Pakistan and Sri Lanka. Community engagement for national scale-up of COBRA-BPS is likely to be successful in all three countries.